Video Pre-production for Low-Budget Films. - Angel, Eduardo (linkedin.com, 2016)
Learn pre-production steps for low-budget and ultra-low-budget films. Emmy-winning director Eduardo Angel covers the entire pre-production workflow, from concepting to pre-shooting.